Microwave irradiation time-dependent tuning of the physicochemical properties and photocatalytic activity of SnO2 quantum dots for tetracycline photodegradation - Seow Ching Phoon; Anwar Iqbal; Junichi Ida; Dede Heri Yuli Yanto; Muhammad Rahimi Yusop; M. Hazwan Hussin; Kalaivizhi Rajappan (Results in Engineering)
The effectiveness of semiconductor quantum dots (QDs), particularly SnO2 QDs, in photocatalysis is dependent on synthesis parameters. Microwave irradiation time significantly influences nucleation, crystallinity, defect concentration, and pore structure, which directly affect photocatalytic efficiency. Despite its critical role, the impact of microwave irradiation time is often treated as a constant parameter. This study systematically investigates the impact of microwave irradiation time (3, 5, and 7 min at 600 W) on the physicochemical properties and photocatalytic activity of SnO2 QDs for tetracycline (TC) photodegradation. TC is a persistent antibiotic frequently detected in wastewater and poorly removed by conventional treatment due to its high solubility and chemical stability. SnO₂ QDs synthesized at 3 min (SnO2 QDs-3 min) exhibited the smallest particle size (2.1 nm), narrowest band gap (3.44 eV), and a micro-mesoporous structure (DFT pore size 2.30–10.5 nm) formed through QD aggregation during drying. Despite its relatively low BET surface area (111.62 m²/g), this sample showed superior TC removal, attributed to enhanced light absorption, efficient charge separation, and increased surface reactivity due to low crystallinity. PL and EIS analyses confirmed the lowest electron-hole recombination rate and highest conductivity for SnO2 QDs-3 min. Under optimal conditions (100 mg catalyst, 10 mg/L TC, pH 8.5, 90 min under fluorescent light), complete TC removal was achieved. Scavenging test identified electrons (e−), holes (h+) and hydroxyl radicals (HO•) as the primary species. However, reusability tests revealed reduced performance (35 % removal), likely due to Na+/Cl− leaching and pore structure alteration.